Dynamics of Myocardial Remodeling Activity Markers in Patients with Myocardial Infarction with Persistent ST-Segment Elevation on the Background of Multivascular Coronary Artery Disease Depending on Diagnostic and Treatment Tactics - Uzun, D. Yu.; Uzun, K. S.; Lazoryshynets, V. (Ukrainian Journal of Cardiovascular Surgery, 2021)
In patients with myocardial infarction with stable ST-segment elevation, the gold standard is to perform emergency angiography and stenting of the infarct-dependent artery. Meanwhile, the existing recommendations do not contain spe-cific treatment and diagnostic tactics for multivascular coronary pathology. The aim. To analyze the influence of different tactical approaches to the correction of multivascular atherosclerotic lesions of the coronary arteries on the processes of myocardial remodeling. Materials and methods. The study included 102 patients with multivascular coronary artery disease, who were randomly divided into 4 observation groups. The 1st group included 25 (24.5%) patients who had coronary angiography with occlusion of the infarct-dependent vessel and urgent stenting. Later, on day 2-3, the presence of hemodynamically significant stenosis of infarct-independent arteries was proved by determining fractional flow reserve and coherent to-mography with assessment of stability, size, length of atheroma and delayed stenting of these vessels. The 2nd group of observations included 26 (25.5%) patients who underwent stenting of the infarct-dependent artery, and on day 2-3 after the study of fractional flow reserve, but without optical coherence tomography, stenting of the infarct-independent vessel. The 3rd group included 25 (24.5%) patients who underwent simultaneous stenting of infarct-dependent and infarct-independent vessels after coronary angiography without additional angiographic studies (fractional flow reserve and coherent tomography). The 4th group included 26 (25.5%) patients who underwent only standard stenting of the infarct-dependent vessel and who were discharged from the department without further study of the circulation in the infarct-independent arteries and without interventions on them. All the patients received standard two-component an-tiplatelet therapy (acetylsalicylic acid 75-150 mg/day and clopidogrel 75 mg/day) and received atorvastatin 20 mg and ezetimibe 10 mg. The results obtained in patients were compared with similar results in 30 practically healthy people of the same age and sex. Markers of left ventricular myocardial remodeling activity were investigated by determining blood levels of matrix metalloproteinase-1 (MMP-1) and its tissue inhibitor 1 (TIMP-1). Results. Interventions without additional angiographic studies with complete revascularization of infarct-indepen-dent vessels (group 4) contributed to the long-term maintenance of the highest activity of MMP-1 against the background of virtually no activity of TIMP-1. Simultaneous stenting of the infarct-dependent and infarct-independent arteries only by the results of coronary angiography (group 3) contributes only to a slow decrease in the activity of metalloproteinase against the background of a slight increase in the activity of its inhibitor. Stenting of the infarct-dependent artery after coronary angiography with the study of only the fractional flow reserve without coherent tomography contributed to more active inhibition of metalloproteinase activity against the background of increase in concentrations of its inhibitor. The most active in relation to laboratory markers of myocardial remodeling was the tactic using angiographic examina-tion, determination of fractional flow reserve and coherent tomography, followed by a complete set of delayed revascu-larization. The use of delayed treatment of infarct-independent arteries using additional diagnostic techniques (study of fractional flow reserve and coherent tomography) can affect the activity of metalloproteinase 1 and its tissue inhibitor which are markers of activity of postinfarction remodeling.